2022
DOI: 10.1155/2022/9097530
|View full text |Cite
|
Sign up to set email alerts
|

From Hair to Colon: Hair Follicle-Derived MSCs Alleviate Pyroptosis in DSS-Induced Ulcerative Colitis by Releasing Exosomes in a Paracrine Manner

Abstract: Ulcerative colitis (UC) has attracted intense attention due to its high recurrence rate and the difficulty of treatment. Pyroptosis has been suggested to be crucial in the development of UC. Although mesenchymal stem cells (MSCs) are broadly used for UC therapy, they have rarely been studied in the context of UC pyroptosis. Hair follicle-derived MSCs (HFMSCs) are especially understudied with regard to UC and pyroptosis. In this study, we aimed to discover the effects and potential mechanisms of HFMSCs in UC. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The inhibition of pyropto-sis in dextran sulfate sodium-induced ulcerative colitis in mice by transplantation of hair follicle-derived MSCs is critically associated with exosomes produced by mesenchymal cells since the inhibition of exosome secretion completely abolishes the protective effects of the MSCs in vivo and in vitro. Presumably, MSC-derived exosomes might inhibit pyroptosis through tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) signaling and the IFN-γ pathway [249]. Also, many studies have shown that miRNAs transported by MSCderived exosomes play a role in the suppression of pyroptosis caused by inflammation or other stimuli [250].…”
Section: Anti-ferroptosis and Anti-pyroptosis Effects Of Mscmentioning
confidence: 99%
“…The inhibition of pyropto-sis in dextran sulfate sodium-induced ulcerative colitis in mice by transplantation of hair follicle-derived MSCs is critically associated with exosomes produced by mesenchymal cells since the inhibition of exosome secretion completely abolishes the protective effects of the MSCs in vivo and in vitro. Presumably, MSC-derived exosomes might inhibit pyroptosis through tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) signaling and the IFN-γ pathway [249]. Also, many studies have shown that miRNAs transported by MSCderived exosomes play a role in the suppression of pyroptosis caused by inflammation or other stimuli [250].…”
Section: Anti-ferroptosis and Anti-pyroptosis Effects Of Mscmentioning
confidence: 99%